Traits of Exogenous Species and Indigenous Community Contribute to the Species Colonization and Community Succession - Tao, Jiemeng; Qin, Chong; Feng, Xue; Ma, Liyuan; Liu, Xueduan; Yin, Huaqun; Liang, Yili; Liu, Hongwei; Huang, Caoming; Zhang, Zhigang; Xiao, Nengwen; Meng, Delong (Frontiers in Microbiology, 2018)
Introducing exogenous species into an indigenous environment is an effective method to strengthen the ecological functions. The traits of the exogenous species and the indigenous communities, as well as the resistance and subsequent succession of community to exogenous species are not well understood. Here, three different functional consortia were introduced into two extremely acidic systems, leaching heap (LH) and leaching solution (LS), deriving from the Zijin copper mine, China. The results showed that the structures of both LS and LH communities were affected by the three consortia, but not all the structural changes were in line with variations of community function. Among the three consortia, only the complementary sulfur oxidizers greatly enhanced copper extraction efficiency of LS by 50.42%. This demonstrated that functional niche novelty gave exogenous species an advantage to occupy an ecological niche in a complementarily manner, thus, leading to successful colonization. The resistance to, and subsequent succession by, exogenous organisms varied between the two indigenous communities. To be specific, the LS community with low community diversity and simple composition was susceptible to exogenous species, and the community structural changes of LS were both divergent and irreversible. In comparison, the LH community with higher community diversity and more complex composition, was more resistant to exogenous species, with the community structures showing a convergent trend over time despite different species being introduced. Therefore, we propose that diverse communities compete for resources more intensely with exogenous species and resist to their introduction, and that communities with complex composition are able to cope with exogenous disturbances.